حتمية الذكاء الاصطناعي في التسويق الرقمي - بركاهم كموش; شهرزاد نسيب (University of Eloued جامعة الوادي, 2022)
نهدف من خلال دراستا إلى التعرف على التطبيقات والتقنيات التي يستخدمها الذكاء الاصطناعي والتي تلائم مجال التسويق الرقمي، خصوصا وأن العالم يعيش انفجارا تكنولوجيا وتقدما هائلا في التحول الرقمي وثورة المعلومات. سنحاول من خلال هذه الورقة البحثية تسليط الضوء على الذكاء الاصطناعي ومدى حتميته في التسويق الرقمي من خلال معرفة أهم تطبيقاته وتقنياته التي سبق واستخدمت في مختلف الشركات والمؤسسات. حيث اعتمدنا على دراسة وصفية للنماذج الخاصة بالذكاء الاصطناعي في التسويق الرقمي، حيث مكننا ذلك من الإجابة على التساؤل المطروح وبالتالي توصلنا إلى مجموعة من النتائج من أبرزها أن الذكاء الاصطناعي يعتبر اليوم تحدي كبير وضرورة لا بد منها بالنسبة للمؤسسات بمختلف أنواعها وأحجامها وأشكالها تضمن من خلاله البقاء والاستمرارية Abstract: hrough Ttwo studies, we aim to identify the applications and techniques used by artificial intelligence that are appropriate in the field of digital marketing, especially as the world is experiencing a technological explosion and tremendous progress in digital transformation and the information revolution. Through this research paper, we will try to shed light on artificial intelligence and its inevitability in digital marketing by knowing its most important applications and techniques that have previously been used in various companies and institutions. Where we relied on a descriptive study of models for artificial intelligence in digital marketing, as this enabled us to answer the question posed and thus reached a set of results, the most prominent of which is that artificial intelligence today is a great challenge and an imperative necessity for organizations of all kinds, sizes and shapes that ensure survival, and continuity.
The imperative of artificial intelligence in digital marketing
مداخلة. الملتقى الدولي الافتراضي حول: البيانات الضخمة والاقتصاد الرقمي كآلية لتحقيق الإقلاع الاقتصادي في الدول النامية "الفرص، التحديات والآفاق"
Keywords: الذكاء الاصطناعي، التسويق الرقمي، الانترنيت، التكيف الرقمي; Artificial Intelligence, Digital Marketing, Internet, Digital Adaptation